2005
DOI: 10.1159/000081222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Menstrual Cycle on Postoperative Analgesic Requirements, Agitation, Incidence of Nausea and Vomiting after Gynecological Laparoscopy

Abstract: Background: Several studies have suggested that the menstrual cycle has an impact on postoperative nausea and vomiting (PONV). No previous study has evaluated the effect of the menstrual cycle on the incidence of postoperative agitation and analgesic/antiemetic requirements. Methods: On the basis of the phase of the menstrual cycle [pre±menstrual (Pd 25–6), early follicular phase (Pd 8–12), ovulatory phase (Pd 13–15), and luteal phase (Pd 20–24)], 67 patients enrolled in this blinded, prospective study. Anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 28 publications
3
28
0
2
Order By: Relevance
“…In the early postoperative period, the incidence of nausea but not of vomiting was decreased during the luteal phase. The results of this study were similar to studies that suggested that the early phase of the cycle increases risk of PONV [9][10][11], but differed with those that determined that the luteal phase was a predictor of PONV [12,13] and likewise to those studies that found no influence of the cycle on PONV [14,16,17]. Small, single-center studies may not have enough power to answer the question, but a subsequent metaanalysis may be helpful.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In the early postoperative period, the incidence of nausea but not of vomiting was decreased during the luteal phase. The results of this study were similar to studies that suggested that the early phase of the cycle increases risk of PONV [9][10][11], but differed with those that determined that the luteal phase was a predictor of PONV [12,13] and likewise to those studies that found no influence of the cycle on PONV [14,16,17]. Small, single-center studies may not have enough power to answer the question, but a subsequent metaanalysis may be helpful.…”
Section: Discussionsupporting
confidence: 64%
“…While the follicular phase of the menstrual cycle increased the risk for PONV in some studies [9][10][11], the luteal phase increased the risk in another [12]. Moreover both phases, follicular and luteal increased the risk in one study [13] but not in a multicentre study [14] or a factorial trial of six interventions for the prevention of PONV (IMPACT study) [8] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Also, women are more susceptible to PONV, especially menstruating women, because of a higher level of sexual hormones (e.g., gonadotropin, and mainly progesterone) than in men [2,7,13,16,18]. It is also noteworthy that athletic patients and younger patients, especially children 11 to 16 years of age, are more susceptible to PONV, and the risk decreases with the patientÕs age [4,6,9,15].…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of women report increases in pain-related symptoms at certain stages of the menstrual cycle [5]. Anesthetic, analgesic, and antiemetic requirements also change across the menstrual cycle [6][7][8]. Several factors have been suggested to explain this situation.…”
Section: Introductionmentioning
confidence: 99%